Persons viewing the TLA Exhibition - Richardson, Dennis (1981)
This is a black and white photograph of persons viewing the TLA Exhibition.
Copyright- API. Daily News collection, no restriction.
Keywords: Exhibition, Ja- TLA for library week; Photograph